Proceedings of SPE Permian Basin Oil and Gas Recovery Conference 2000
DOI: 10.2523/59535-ms
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Xanthan Gum in Fluid-Loss Control and Related Formation Damage

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractXanthan gum has been used extensively in the oil industry as a viscosifier for different applications due to its unique rheological properties. In this paper we explore how the rheological behavior of xanthan-based fluids can be used to control fluid loss. Linear and radial flow tests were performed in 100-1,000 md rocks. The rheological characteristics of xanthan gum were measured in linear core flow tests. This constitutive flow behavior was used in a radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Fluid loss control in solids-free brines is generally achieved by; increasing the viscosity of the fluid [5][6][7][8][9][10][11][12][13][14][15][16] and developing internal/external filter cake using lost control additives 17 . In a recent study, Svendsen et al 18 has shown that extensional viscosity can be successfully used to establish an internal filter cake in association with a coiled tubing drilling fluid application.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid loss control in solids-free brines is generally achieved by; increasing the viscosity of the fluid [5][6][7][8][9][10][11][12][13][14][15][16] and developing internal/external filter cake using lost control additives 17 . In a recent study, Svendsen et al 18 has shown that extensional viscosity can be successfully used to establish an internal filter cake in association with a coiled tubing drilling fluid application.…”
Section: Introductionmentioning
confidence: 99%
“…The excess pressure drop may be due to the substantial extensional component present in this flow configuration (Khan et al, 2003;Durst et al, 1987;Jones and Walters, 1989;Saasen et al, 1990;Navarrete et al, 2000). Naverrete and Mitchell (1995) suggested that for the XG solutions, the flow was dominated by the shear viscosity, whereas for the PHPA solutions the flow was dominated by the extensional viscosity.…”
Section: Introductionmentioning
confidence: 93%
“…Naverrete et al 14 , suggested that for the xanthan gum solutions the flow was dominated by the shear viscosity, whereas for the PHPA solutions the flow was dominated by the extensional viscosity, especially, at high-enough extensional rates.…”
Section: Introductionmentioning
confidence: 97%
“…It has been recognized that the excess pressure drop may be due to the substantial extensional component present in this flow configuration. [5][6][7][8][9][10][11][12][13][14] Durst et al 8 , for example, suggested that as much as 75 % of the pressure losses in the formation may result from extensional viscosity.…”
Section: Introductionmentioning
confidence: 99%